Melting hadrons, boiling quarks : from Hagedorn temperature to ultra-relativistic heavy-ions collisions at CERN : with a tribute to Rolf Hagedorn /: from Hagedorn temperature to ultra-relativistic heavy-ions collisions at CERN : with a tribute to Rolf Hagedorn. ([2016]) - Unknown
No abstract available